Analisis Tegangan Roll Untuk Produksi Baja Tulangan Beton Tahap Roughing Menggunakan Metode Finite Element Analysis - Agung Fauzi Hanafi; Ardi Mahardika; Asmar Finali; Mega Lazuardy Umar; Rochmad Eko PU (P3M Politeknik Negeri Cilacap, 2024)
Concrete reinforcing steel is alloy steel with a round cross section using a plain or fin surface and produced from a material called billet. The production process for concrete reinforcing steel generally uses a rolling process. The stress on the roll that is generated during the rolling process is something that needs to be considered. Stresses that exceed the fatigue limit will result in failure and even damage to the roll. This research aims to determine the maximum stress in rolls at the roughing stage, namely roll 1H, roll 2H, and roll 1 with standard sizes. By using the Finite Element Analysis simulation, it is expected that it can provide recommendations for the maximum roll stress produced in the rolling process. From the simulations carried out, the maximum stress value for roll 1H is 190.34 MPa, roll 2H is 227.28 MPa and roll 1 is 136.18 MPa. The stress that occurs in the roll is considered safe because it is below the fatigue stress value of the roll material.